2021
DOI: 10.47895/amp.v55i2.2845
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Factors Associated with Mortality of 200 COVID-19 Patients at a Philippine COVID-19 Tertiary Referral Center

Abstract: Objectives: To describe the clinical profile and factors associated with mortality among the first 200 patients confirmed to have COVID-19 infection admitted in the University of the Philippines – Philippine General Hospital (UP-PGH)  Methodology: We conducted a retrospective review of adult patients with confirmed COVID-19 infection admitted in PGH, a designated COVID-19 referral center.  Demographic, clinical data, and clinical outcomes were extracted from medical records. Frequencies and distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Although only 79 patients were included in our COVID-TB research, our study revealed worse outcomes in terms of ICU stay, proportion of patients needing invasive ventilation, and case fatality rate as well as length of hospital stay among non-survivors compared to the study of Salamat and colleagues 10 among 200 COVID-19 patients admitted in our institution ( Table 2 ). The same dismal outcomes were also demonstrated by published studies on COVID-TB.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although only 79 patients were included in our COVID-TB research, our study revealed worse outcomes in terms of ICU stay, proportion of patients needing invasive ventilation, and case fatality rate as well as length of hospital stay among non-survivors compared to the study of Salamat and colleagues 10 among 200 COVID-19 patients admitted in our institution ( Table 2 ). The same dismal outcomes were also demonstrated by published studies on COVID-TB.…”
Section: Discussionmentioning
confidence: 70%
“…Cardiovascular, metabolic, and respiratory comorbidities were relatively more common among COVID-19 patients especially among those with a more severe clinical course. 7 , 8 , 10 , 13 Diabetes and hypertension were isolated by earlier studies as risk factors in the development of severe to critical forms of COVID-19 and were recommended to be part of the routine screening tests. 5 , 10 Diabetes and any factor which may contribute to a poor immune system of an individual, like HIV, may also pose significant risks in the pathogenesis of TB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 COVID-19 was classified as mildpatients with symptoms of COVID-19 without pneumonia; moderate -patients with clinical and radiographic evidence of pneumonia but not requiring oxygen; severe -patients with clinical and radiographic evidence of pneumonia with oxygen saturation <92% on room air and requiring oxygen support; critical -patients with ARDS, septic shock, requiring mechanical ventilation and admission to the intensive care unit (ICU) or both. 14,15 For this study, liver injury (LI) was defined as an elevation of ALT above the upper limit of normal (normal value was based on the institutional cut-off of 50 u/L) at any time during admission. ALT was chosen over AST because it is more specific to the liver.…”
Section: Variables and Outcomesmentioning
confidence: 99%